The role of iron metabolism as a mediator of macrophage inflammation and lipid handling in atherosclerosis - Habib, Anwer; Finn, Aloke V. (Frontiers in Pharmacology, 2014)
Iron is an essential mineral needed for normal physiologic processes. While its function in oxygen transport and other important physiologic processes is well known, less is understood about its role in inflammatory diseases such as atherosclerosis. Existing paradigms suggest iron as a driver of atherosclerosis through its actions as a pro-oxidant capable of causing lipid oxidation and tissue damage. Recently we and others have identified hemoglobin derived iron as an important factor in determining macrophage differentiation and function in areas of intraplaque hemorrhage within human atherosclerosis. Hemoglobin associated macrophages, M(Hb), are distinct from traditional macrophage foam cells because they do not contain large amounts of lipid or inflammatory cytokines, are characterized by high levels of expression of mannose receptor (CD206) and CD163 in addition to producing anti-inflammatory cytokines such as IL-10. Despite the well-known role of iron as an catalyst capable of producing lipid peroxidation through generation of reactive oxygen species such as hydroxyl radical, we and others have shown that macrophages in areas of intraplaque hemorrhage demonstrate reduced intracellular iron and reactive oxygen species (ROS) which triggers production of anti-inflammatory cytokines as well as genes involved in cholesterol efflux. These data suggest that manipulation of macrophage iron itself may be a promising pharmacologic target for atherosclerosis prevention through its effects on macrophage inflammation and lipid metabolism. In this review we will summarize the current understanding of iron as it relates to plaque inflammation and discuss how further exploration of this subject may lead to new therapies for atherosclerosis.